Slave-owners’ Compensation: The Bahamas Colony - Saunders, Olivia C. (International Journal of Bahamian Studies, 2019)
This study uses descriptive statistics to provide an overview of the compensation received by former slave-owners who were compensated for the loss of their property in the Bahamas colony, that is, their slaves, after Emancipation. The data used for this study is from the University College London’s Legacies of British Slave-ownership Centre. This paper answers four questions: What was the amount of the compensation received by former slave-owners in the Bahamas colony in 1834? What was the distribution of the compensation? What is the 2017 price equivalent of the compensation paid? What would be the investment value of the compensation in 2017 using prevailing interest rates? It is shown that 1,057 awardees received £126,848.70 for 10,087 slaves in 1834. There were six different types of awardees based on the type of ownership. The 2017 equivalent of the total compensation using prices, equates to £11,588,494.36 and in terms of investment value, equates to £342,031,365.63.